The Impact of Size on the Performance of Transnational Corporations Operating in the Textile Industry in Portugal during the COVID-19 Pandemic - Santos, Eleonora (2022)
The aim of this work is to understand the impact of size on the performance of transnational corporations (TNCs) operating in the textile and clothing industry in Portugal during the COVID-19 pandemic. For this purpose, we used ORBIS data for the period 2019–2020 and narrative, financial and correlation analyses to assess the performance of five companies. Thus far, the impact of company size on the competitiveness of Portuguese textile affiliates during the pandemic has remained unexplored. The results show that smaller firms performed better than larger ones, likely due to the higher fixed costs of the latter at times when orders declined worldwide. Our analysis suggests that there are some characteristics of TNCs that matter in explaining company-level performance during crises, such as management experience and flexibility. Furthermore, as Portugal is a major European textile exporter, it is useful for the host country to assess the economic sustainability of its foreign investors. The results provide some policy recommendations regarding the promotion of foreign direct investment (FDI) in Portugal.